Prispevek Davorina Jenka k slovenskemu samospevu - Smrekar, Borut (Muzikološki zbornik, 2006)
In the article, the songs of one of the key 19th century Slovene composers are analysed. Attention focuses on problems, and solutions, of chronology, on the choice of texts, and the analysis of the compositional realizations, which aims at setting them into the contemporary European and Slovene receptional context.
Keywords: 19.st.; glasba; Jenko, Davorin, 1835-1914; music; samospev; Slovenia; Slovenija